Прогнозирование уровня смертности от инфекции Mpox в Африке с использованием гибридного подхода - Djillali Seba (Журнал инфектологии, 2025)
Objective: The main objective of our work is to forecast the daily Infection Fatality Rate (IFR) index for Mpox, a disease that has posed significant challenges, particularly in African countries. Mpox has become a major public health concern due to its rapid spread and the strain it places on healthcare systemsMethods: In this paper, we use a hybrid approach to enhance the performance of traditional models. First, we apply the ARIMA model, which is more suitable for the task, and then we implement a noise reduction technique to further improve the results.Results and discussions: We utilize four performance measures RMSE, MSE, MAE, and MAPE to evaluate the efficiency of our approach. By combining a denoising technique with ARIMA and integrating Singular Spectrum Analysis (SSA) with the ARIMA model, the SSA-ARIMA model demonstrates the best performance.Conclusion: Forecasting the Infection Fatality Rate with an appropriate model provides a deeper understanding of this phenomenon, enabling authorities to effectively control and manage the risks associated with Mpox.